Metodologia para diagnóstico da interferência da cultura organizacional nos elementos da gestão da qualidade - Pereira, Tafael Lucas (2020)
The failure cases resulting from the quality management implementation initiatives have stimulated the development of research considering as a possible cause the failure to address conceptual factors in organizational strategies. The organizational culture appears as a possible factor in the involvement of the quality system effectiveness. Thus, the objective of the study was to develop a methodology for measuring the interference of organizational culture in the effectiveness of the quality management system. Starting with a systematic review using the Methodi Ordinatio, followed by the determination of the Contextual Factors for measuring the relationship, delimitation of the theoretical relationship model, construction of the measurement tool and the application of the tool in health institutions with quality seals. It was also evident that the different elements of quality are related to more than one type of culture, highlighting the pluralist view of quality management, taking into account cultural multiplicity. The measurement tool developed is in the form of a questionnaire based on 57 affirmative questions that represent the distinct cultural characteristics necessary for the effectiveness of the elements of quality. The questionnaire can be shaped according to the reality of the organization or according to what elements you want to analyze. Analyzing the results of the application in health institutions, the companies presented MODA referring to the Average interference aspect, which characterizes that for all the Soft and Hard elements of quality tested, in the five Contextual Factors the percentage result of interference did not exceed 45%. However, the result indicates a variability in results between companies, which may lead to future studies to verify the institutions individually, applying to all employees.